2016
DOI: 10.1007/978-3-319-45875-5_18
|View full text |Cite
|
Sign up to set email alerts
|

A Unified View of LIBOR Models

Abstract: We provide a unified framework for modeling LIBOR rates using general semimartingales as driving processes and generic functional forms to describe the evolution of the dynamics. We derive sufficient conditions for the model to be arbitrage-free which are easily verifiable, and for the LIBOR rates to be true martingales under the respective forward measures. We discuss when the conditions are also necessary and comment on further desirable properties such as those leading to analytical tractability and positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The definition of multiple curve affine LIBOR models implies that the dynamics of OIS forward rates and forward LIBOR rates, more precisely of 1 + δ x F x k and 1 + δ x L x k , exhibit an exponential-affine dependence in the driving process X; see (3.5) and (3.8). Glau, Grbac, and Papapantoleon (2016) recently showed that models that exhibit this exponential-affine dependence are the only ones that produce structure preserving LI-BOR models; cf. Proposition 3.11 therein.…”
Section: Affine Libor Models With Multiple Curvesmentioning
confidence: 99%
“…The definition of multiple curve affine LIBOR models implies that the dynamics of OIS forward rates and forward LIBOR rates, more precisely of 1 + δ x F x k and 1 + δ x L x k , exhibit an exponential-affine dependence in the driving process X; see (3.5) and (3.8). Glau, Grbac, and Papapantoleon (2016) recently showed that models that exhibit this exponential-affine dependence are the only ones that produce structure preserving LI-BOR models; cf. Proposition 3.11 therein.…”
Section: Affine Libor Models With Multiple Curvesmentioning
confidence: 99%
“…The last financial crisis (2007)(2008) has greatly increased the monitoring and pricing of CCR on OTC-markets products and many researchers and practitioners tried to develop a general framework for a better assessment of the CVA evaluation to compensate a derivatives holder for taking CCR. Indeed, along the years, other value adjustments have been additionally considered leading to the acronym (X)VA. An updated overview of the recent research directions under investigation is presented in [15].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, models based on a forward process are able to better describe market dynamics than market models can, and a driving Lévy process is generally more suitable for capturing market fluctuations than the classical Black-Scholes model (Black and Scholes 1973, Henrard 2005, Hilber et al 2009. More importantly, the LFPM is in fact capable of dealing with negative LIBOR rates (Glau et al 2016).…”
Section: Introductionmentioning
confidence: 99%